Mind and motion : the bidirectional link between thought and action - Raab, Markus; Johnson, Joseph G.; Heekeren, Hauke R.; ScienceDirect eBooks (Amsterdam ; Boston : Elsevier, 2009)
An interdisciplinary look at the interaction between the mind and body in motion.
How are the choice options and their consequences perceived and represented? -- Grounding cognition in action: expertise, comprehension, and judgment -- On the relativity of athletic performance: a comparison on performance judgments in sports -- Cognitive movement scientist's view on the link between thought and action: insights from the Badische Zimmer metaphor -- Perceiving and moving in sports and other high-pressure contexts -- How do people perceive and generate options? -- How the orbitofrontal cortex contributes to decision making: a view from neuroscience -- Perceiving the intentions of others: how do skilled performers make anticipation judgments? -- Bidirectional links between decision making, perception, and action -- How are these options evaluated and an intended course of action selected? -- Irrationality in action: do soccer players and goalkeepers fail to learn how to best perform during a penalty kick? -- Getting around: making fast and frugal navigation decisions -- Crossmodal interaction in speeded responses: time window of integration model -- Embodied cognition of movement decisions: a computational modeling approach -- Multiple-cue learning approach as the basis for understanding and improving soccer referees' decision making -- Conceptual framework for studying emotions-cognitions-performance linkage under conditions that vary in perceived pressure -- Visual cues influence motor coordination: behavioral results and potential neural mechanisms mediating perception-action coupling and response selection -- How do motoric realities shape, and become shaped by, the way people evaluate and select potential courses of action? Toward a unitary framework of embodied decision making -- How is a cognitively intended course of action physically implemented? -- Perceptual decision making: a bidirectional link between mind and motion -- Motor imagery and its implications for understanding the motor system -- Cognitive nature of action: functional links between cognitive psychology, movement science, and robotics -- Mental representations as an underlying mechanism for human performance -- Biases and optimality of sensory-motor and cognitive decisions -- Advances in coupling perception and action: the quiet eye as a bidirectional link between gaze, attention, and action -- Juggling with the brain: thought and action in the human motor system -- How are actions physically implemented? -- Mind and motion: surveying successes and stumbles in looking ahead.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Brain; Nervous system; Brain -- Research; Nervous system -- Research; MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; Brain; Brain -- Research; Nervous system; Nervous system -- Research; Bewegung; Motorisches Lernen; Cognition; Decision Making; Motion; Humans; Electronic books